Une nouvelle source arabe sur l’océan Indien au Xe siècle : le Ṣaḥīḥ min aḫbār al-biḥār wa-‘aǧā‘ibihā d’Abū ‘Imrān Mūsā ibn Rabāḥ al-Awsī al-Sīrāfī - Jean-Charles Ducène (Afriques)
While The Book of the Wonders of India was an important evidence about commercial relations in the Indian Ocean in the tenth century, its author remained subject to debate. The version given by al-‘Umarī (fourteenth century) makes possible determine the author of this collection of stories and in addition it provides new anecdotes that bring original information about South-East Asia but little about East Africa, except on Zayla‘ and perhaps Austronesian expeditions towards Africa.